2016
DOI: 10.1200/jco.2015.63.9161
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Alterations and Everolimus Efficacy in Human Epidermal Growth Factor Receptor 2–Overexpressing Metastatic Breast Cancers: Combined Exploratory Biomarker Analysis From BOLERO-1 and BOLERO-3

Abstract: This analysis, although exploratory, suggests that patients with human epidermal growth factor receptor 2-positive advanced breast cancer having tumors with PIK3CA mutations, PTEN loss, or hyperactive PI3K pathway could derive PFS benefit from everolimus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 26 publications
5
105
0
1
Order By: Relevance
“…Biomarker analysis of two phase III trials (BOLERO-1 and BOLERO-3) that randomized Her2-positive breast cancer patients to receiving a chemotherapy with and without everolimus revealed that participants with an altered PI3K pathway had a statistically improved PFS with an everolimus-containing regimen (hazard ratio [HR]: 0.67; 95% confidence interval [CI], 0.48–0.93), while there was no benefit from everolimus among patients with wild-type PI3K pathway (HR: 1.19; 95% CI, 0.87–1.62) (46). Janku et al have also reported that, among diverse malignancies, PIK3CA or PTEN alterations were the independent factor predicting response to inhibitors targeting PI3K pathway, including mTor inhibitors, albeit when used in combination therapy rather than as single agents (47).…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker analysis of two phase III trials (BOLERO-1 and BOLERO-3) that randomized Her2-positive breast cancer patients to receiving a chemotherapy with and without everolimus revealed that participants with an altered PI3K pathway had a statistically improved PFS with an everolimus-containing regimen (hazard ratio [HR]: 0.67; 95% confidence interval [CI], 0.48–0.93), while there was no benefit from everolimus among patients with wild-type PI3K pathway (HR: 1.19; 95% CI, 0.87–1.62) (46). Janku et al have also reported that, among diverse malignancies, PIK3CA or PTEN alterations were the independent factor predicting response to inhibitors targeting PI3K pathway, including mTor inhibitors, albeit when used in combination therapy rather than as single agents (47).…”
Section: Discussionmentioning
confidence: 99%
“…In this trial, amplification of cyclin D1 had no impact on everolimus efficacy, whereas mutation or amplification of FGFR1 or FGFR2 resulted in less benefit from everolimus treatment, though the trial was not sufficiently powered to deliver definitive conclusions in this regard. A meta-analysis of the BOLERO-1 and BOLERO-3 phase 3 trials of everolimus or placebo in combination with trastuzumab and chemotherapy (paclitaxel or vinorelbine, respectively) in patients with HER2+ advanced breast cancer revealed a significant PFS benefit from everolimus in patients with either PIK3CA mutation or low PTEN expression (by IHC), whereas patients with neither of these alterations experienced no PFS benefit from the addition of everolimus (André et al, 2016). …”
Section: Therapeutic Targeting Of the Pi3k Pathway In Cancermentioning
confidence: 99%
“…In vitro studies showed that mTOR activation was related to HER2 overexpression and responsible for HER2-positive breast cancer progression. A recent randomized phase 3 study (BOLERO 3) was designed to compare the efficacy of everolimus plus trastuzumab and vinorelbine with trastuzumab and vinorelbine combination in trastuzumab-resistant HER2-positive MBC patients [26]. In this study, 100% of patients were previously treated with taxanes plus trastuzumab and 28% of patients were previously treated with lapatinib.…”
Section: Discussionmentioning
confidence: 99%